PEMBUATAN BIOADSORBEN DARI KOMBINASI KITOSAN DAN KULIT JAGUNG PADA PROSES PEMURNIAN MINYAK JELANTAH - Adzani Ghani Ilmannafian; Muhammmad Indra Darmawan; Mariatul Kiptiah; Hasnan Bukhari (EnviroScienteae, 2023)
Adsorbent is a solid substance that can absorb certain components from a fluid phase. Adsorbents consist of materials that are porous and directly hit the pore walls at a pertical location. The purpose of this final project is to see whether the purification of used cooking oil with the adsorbent method using a mixture of corn husk and shrimp shell chitosan adsorbents in several comparisons has an effect in purifying used cooking oil. This research was conducted by adsorption method of used cooking oil samples using corn husk bioadsorbent and shrimp shell chitosan. The use of this used cooking oil adsorbent process is so that used cooking oil that is no longer suitable for use in the community can be reused. Then proceed with the adsorption process starting with 100 ml of oil added 5 g of adsorbent with variations in the mass ratio of chitosan and corn husk = ((25: 75), (50: 50), and (75:25)%) stirring constantly for 90 minutes with temperature 70-80 C. The best results based on SNI cooking oil are in a ratio of 3,5 g: 1,5 g to 5 grams of adsorbent used or at a ratio of 75% corn husk adsorbent: 25% shrimp shell chitosan, with an acid number of 0,62 mg KOH /g, the free fatty acid compound is 0,80% and the peroxide number is 6,36 meq 02/kg.